Teaching the Difficult Heritage of Italian Fascism - Malone, Hannah (My University, 2023)
In recent years, the architectural legacy and so-called ‘difficult heritage’ of Fascist Italy has become a flourishing field of research. These topics have also begun to make their way into the undergraduate classroom. To date, however, there has been little research carried out into the methods we use to teach the history of Fascism in particular. In this short article, we outline how we have applied problem-based learning and scenario-based learning approaches to tackle this topic. After presenting three assignments, we explain the benefits associated with a PBL/SBL approach, summarised under the headings of interdisciplinarity, creativity and authenticity, before highlighting some aspects on which colleagues may wish to reflect if they are considering adopting a similar approach in their teaching.
PUBLISHED
Keywords: History; Fascism, teaching, pedagogy, difficult heritage, problem-based learning, scenario-based learning; European History